Toxoplasma reactivation after renal transplant – low expression of nitric oxide synthase and a Th2 pattern of immune response - Tuon, Felipe Francisco; Cordeiro, Daiane Maria (Revista Médica da UFPR, 2015)
Background: The mechanism of immunosuppression associated with reactivation of the toxoplasmosis in transplanted patients is known, but the interactions of the human cells and cytokines expression is not well established. Case report: We described a case of toxoplasmosis reactivation in a renal transplanted patient with pneumonitis. The in situ expression of cytokines and cellular phenotypes was evaluated in this case. Results: A Th2 pattern of immune response predominated with strong expression of TGF-beta, TNF-alpha and IL-10. The expression of IL-2 receptor, nitric oxide synthase and IFN-gamma were weak. Conclusion: The reactivation of toxoplasmosis in the lung was associated with a Th2 pattern of immune response and decreased activity of macrophages.